Correction to: Pericardial effusion under nivolumab: case-reports and review of the literature. Issue 1 (2nd December 2019) - Saade, Anastasia; Mansuet-Lupo, Audrey; Arrondeau, Jennifer; Thibault, Constance; Mirabel, Mariana; Goldwasser, François; Oudard, Stéphane; Weiss, Laurence
Abstract : Following publication of the original article [1], the authors reported that authors' given and family names haven been incorrectly tagged.